The relationship between C-reactive protein, anthropometric parameters and lipids in menopausal transition - Dženana Softić; Lejla Mešalić (Medicinski glasnik, 2022)
Aim: To investigate the relationship between C-reactive protein, anthropometric parameters, and lipids in women in the menopausal transition. Methods: This cross-sectional study included 150 women divided into three groups: premenopausal (n=50), perimenopausal (n=50), and postmenopausal (n=50). All women were interviewed, body mass index (BMI) and waist-hip ratio (WHR) values were calculated, and a blood sample was taken for laboratory analysis. The values of the lipids were determined including triglycerides, total cholesterol, and high-density lipoprotein (HDL) cholesterol, while low-density lipoprotein (LDL) and very-low-density lipoprotein (VLDL) cholesterol values were obtained through formulas. The concentration of CRP was determined by immunoturbidimetry on the Architect ci8200 device. Results: The BMI of postmenopausal women was significantly higher than that of premenopausal (p=0.025) and perimenopausal women (p=0.010). The ratio of the waist-hip circumference of postmenopausal women was significantly higher than the ratio of the waist-hip circumference of premenopausal women (p<0.001), as well as that of perimenopausal women (p<0.001). A significant difference in CRP concentration was found only between the postmenopausal and premenopausal groups (p=0.009). CRP significantly positively correlated with BMI in all three groups. A significant positive correlation was found between CRP and WHR in the perimenopause and in the postmenopause group. No significant correlation was found between CRP and lipid parameters in any group. Conclusion: An increase in body weight or obesity in the postmenopausal period, increase in CRP concentration, and positive correlation between these parameters suggest that entering menopause could mean a potential increase in the risk of developing cardiovascular and metabolic diseases.
Keywords: body mass index; inflammation; lipids; menopause; waist-hip ratio